A simple method for implanting free-floating microdevices into the nervous tissue. (26th April 2021) - Khalifa, Adam; Eisape, Adebayo; Coughlin, Brian; Cash, Sydney
Abstract: Objective . Free-floating implantable neural interfaces are an emerging powerful paradigm for mapping and modulation of brain activity. Minuscule wirelessly-powered devices have the potential to provide minimally-invasive interactions with neurons in chronic research and medical applications. However, these devices face a seemingly simple problem—how can they be placed into nervous tissue rapidly, efficiently and in an essentially arbitrary location? Approach . We introduce a novel injection tool and describe a controlled injection approach that minimizes damage to the tissue. Main results. To validate the needle injectable tool and the presented delivery approach, we evaluate the spatial precision and rotational alignment of the microdevices injected into agarose, brain, and sciatic nerve with the aid of tissue clearing and MRI imaging. In this research, we limited the number of injections into the brain to four per rat as we are using microdevices that are designed for an adult head size on a rat model. We then present immunohistology data to assess the damage caused by the needle. Significance . By virtue of its simplicity, the proposed injection method can be used to inject microdevices of all sizes and shapes and will do so in a fast, minimally-invasive, and cost-effective manner. As a result, the introduced technique can be broadly used to accelerate the validation of these next-generation types of electrodes in animal models.